Differentiation of Physiological States under Sensory Deprivation - Iwata, K.; Nakao, M.; Yamamoto, M.; Kimura, M. (Methods of Information in Medicine, 2000)
We attempt to differentiate the physiological state during sensory deprivation (SD) from normal sleep and wakefulness in terms of electroencephalogram (EEG) and heart rate variability (HRV) dynamics. KullbackLeibler (K-L) divergence is employed to quantify differences between their state-dependent dynamics. As a result, the dynamics of EEG and HRV during SD are found to be far distant from any representative dynamics of natural states of sleep and wakefulness. However, relatively speaking, the findings in SD can be categorized into two patterns. (a) The dynamics of HRV during SD is similar to that of rapid eye movement (REM) sleep, and the dynamics of EEG during SD is similar to that of wakefulness. (b) The dynamics of both HRV and EEG during SD are similar to that of REM. Such dissociation between states classified by EEG and HRV dynamics frequently takes place during SD. These findings suggest the peculiarity of the physiological state during the SD distinct from sleep and wakefulness.
Keywords: Sensory Deprivation; Flotation Tank; Multivariate Autoregressive Model; Kullback-Leibler Divergence